Formation of Micrometer‐Sized Textured Hexagonal Silicon Crystals via Nanoindentation - Mouad Bikerouin; Anna Marzegalli; Davide Spirito; Gerald J. K. Schaffar; Corrado Bongiorno; Fabrizio Rovaris; Mohamed Zaghloul; Agnieszka Anna Corley‐Wiciak; Leo Miglio; Verena Maier‐Kiener; Giovanni Capellini; Antonio Massimiliano Mio; et al. (Small Structures)
A comprehensive study on the formation of micrometer‐sized, textured hexagonal diamond silicon (hd‐Si) crystals via nanoindentation followed by annealing is presented. Utilizing advanced characterization techniques such as polarized Raman spectroscopy, high‐resolution transmission electron microscopy, and electron energy‐loss spectroscopy, the successful transformation of silicon into high‐quality hd‐Si is demonstrated. The experimental results are further supported by first‐principles calculations and molecular dynamics simulations. Notably, the hd‐Si phase consists of nanometer‐sized grains with slight misorientations, organized into large micrometer‐scale textured domains. These findings underscore the potential of nanoindentation as a precise and versatile tool for inducing pressure‐driven phase transformations, particularly for the stabilization of hexagonal silicon. The textured nature of hd‐Si also presents a unique opportunity to tailor its optical properties, opening new avenues for its application in semiconductor and optoelectronic devices.